Combination of HDAC and FYN inhibitors in synovial sarcoma treatment - Parker, Kyra; Zhang, Yanfeng; Anchondo, Gavin; Smith, Ashlyn; Guerrero Pacheco, Sergio; Kondo, Tadashi; Su, Le (Frontiers in Cell and Developmental Biology, 2024)
The SS18-SSX fusion protein is an oncogenic driver in synovial sarcoma. At the molecular level, SS18-SSX functions as both an activator and a repressor to coordinate transcription of different genes responsible for tumorigenesis. Here, we identify the proto-oncogene FYN as a new SS18-SSX target gene and examine its relation to synovial sarcoma therapy. FYN is a tyrosine kinase that promotes cancer growth, metastasis and therapeutic resistance, but SS18-SSX appears to negatively regulate FYN expression in synovial sarcoma cells. Using both genetic and histone deacetylase inhibitor (HDACi)-based pharmacologic approaches, we show that suppression of SS18-SSX leads to FYN reactivation. In support of this notion, we find that blockade of FYN activity synergistically enhances HDACi action to reduce synovial sarcoma cell proliferation and migration. Our results support a role for FYN in attenuation of anti-cancer activity upon inhibition of SS18-SSX function and demonstrate the feasibility of targeting FYN to improve the effectiveness of HDACi treatment against synovial sarcoma.